Interspecific Differences in Physiological and Biochemical Traits Drive the Water Stress Tolerance in Young Morus alba L. and Conocarpus erectus L. Saplings - Zikria Zafar; Fahad Rasheed; Ahsan Ul Haq; Faridah Hanum Ibrahim; Shazia Afzal; Mohd Nazre; Seemab Akram; Zafar Hussain; Kamziah Abdul Kudus; Muhammad Mohsin; Abdul Qadeer; Zohaib Raza; et al. (Plants, 2021)
Mitigating climate change requires the identification of tree species that can tolerate water stress with fewer negative impacts on plant productivity. Therefore, the study aimed to evaluate the water stress tolerance of young saplings of C. erectus and M. alba under three soil water deficit treatments (control, CK, 90% field capacity, FC, medium stress MS, 60% FC and high stress, HS, 30% FC) under controlled conditions. Results showed that leaf and stem dry weight decreased significantly in both species under MS and HS. However, root dry weight and root/shoot ratio increased, and total dry weight remained similar to CK under MS in C. erectus saplings. Stomatal conductance, CO2 assimilation rate decreased, and intrinsic water use efficiency increased significantly in both species under MS and HS treatments. The concentration of hydrogen peroxide, superoxide radical, malondialdehyde and electrolyte leakage increased in both the species under soil water deficit but was highest in M. alba. The concentration of antioxidative enzymes like superoxide dismutase, peroxidase, catalase, and ascorbate peroxidase also increased in both species under MS and HS but was highest in C. erectus. Therefore, results suggest that C. erectus saplings depicted a better tolerance to MS due to an effective antioxidative enzyme system.